2018
DOI: 10.21147/j.issn.1000-9604.2018.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation profiles of human B lymphocytes and Epstein-Barr virus-immortalized B lymphocytes

Abstract: Our study demonstrated genome-wide DNA methylation variations between primary B cells and corresponding LCLs, which might yield new insight on the methylation mechanism of EBV-induced immortalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This study reports a comparison of the data generated by Illumina's Infinium MethylationEPIC BeadChip array technology for gDNA from peripheral blood leukocytes from 16 individuals and clDNA, derived from EBV transformation of the same samples into cell lines performed by the ECACC. The methylationEPIC BeadChip array covers 862,927 CpG sites, which makes this the largest gDNA and clDNA methylation profiling study using this array [15]. DNA methylation plays a key role in epigenetic gene regulation and is the most well studied epigenetic factor [16].…”
Section: Discussionmentioning
confidence: 99%
“…This study reports a comparison of the data generated by Illumina's Infinium MethylationEPIC BeadChip array technology for gDNA from peripheral blood leukocytes from 16 individuals and clDNA, derived from EBV transformation of the same samples into cell lines performed by the ECACC. The methylationEPIC BeadChip array covers 862,927 CpG sites, which makes this the largest gDNA and clDNA methylation profiling study using this array [15]. DNA methylation plays a key role in epigenetic gene regulation and is the most well studied epigenetic factor [16].…”
Section: Discussionmentioning
confidence: 99%
“…hypermethylation phenotype in EBV-transformed B cells is not frequently observed (18,69,70), notable methylation patterns in some key TSGs are evident (71). By comparing peripheral primary B cells and the corresponding EBV-transformed B cells, Saha and colleagues showed that EBV infection resulted in four methylation patterns for the TSGs, namely gain of methylation, loss of methylation, distinct methylation, and fluctuating methylation (71).…”
Section: Ebv Transformation Of B Cells Is Associated With Hypomethylamentioning
confidence: 99%
“…This observation was supported by an independent study where the top susceptibility variants for BD were found to be enriched in mQTLs in the cerebellum, but not in transformed lymphocytes ( 90 ). However, as the transformation alters the methylomic landscape of cells, it is unclear how this process impacts methylation levels at mQTL loci and further detection of the enrichment ( 91 ). Candidate gene study of BD risk SNPs in CACNA1C confirmed its risk variants to act as cis- mQTLs in blood ( 92 ).…”
Section: Evidence For the Impact Of Methylation Quantitative Trait Lomentioning
confidence: 99%